2D/2D Graphitic Carbon Nitride (g-C3N4) Heterojunction Nanocomposites for Photocatalysis: Why Does Face-to-Face Interface Matter? - Ong, Wee-Jun (Frontiers in Materials, 2017)
In recent years, two-dimensional (2D) graphitic carbon nitride (g-C3N4) has elicited interdisciplinary research fascination among the scientific communities due to its attractive properties such as appropriate band structures, visible-light absorption, and high chemical and thermal stability. At present, research aiming at engineering 2D g-C3N4 photocatalysts at an atomic and molecular level in conquering the global energy demand and environmental pollution has been thriving. In this review, the cutting-edge research progress on the 2D/2D g-C3N4-based hybrid nanoarchitectures will be systematically highlighted with a specific emphasis on a multitude of photocatalytic applications, not only in waste degradation for pollution alleviation, but also in renewable energy production [e.g., water splitting and carbon dioxide (CO2) reduction]. By reviewing the substantial developments on this hot research platform, it is envisioned that the review will shed light and pave a new prospect for constructing high photocatalytic performance of 2D/2D g-C3N4-based system, which could also be extended to other related energy fields, namely solar cells, supercapacitors, and electrocatalysis.